Comparison between computer-guided and freehand dental implant placement surgery: A systematic review and meta-analysis - Yogui, F. C. [UNESP]; Verri, F. R. [UNESP]; de Luna Gomes, J. M. [UNESP]; Lemos, C. A.A. [UNESP]; Cruz, R. S. [UNESP]; Pellizzer, E. P. [UNESP] (Elsevier, 2020)
The purpose of this systematic review was to compare computer-guided (fully guided) and freehand implant placement surgery in terms of marginal bone loss, complications, and implant survival. This review followed the PRISMA guidelines and was registered in the PROSPERO database (CRD42019135893). Two independent investigators performed the search of the PubMed/MEDLINE, Scopus, and Cochrane Library databases for studies published up to April 2020 and identified 1508 references. After a detailed review, only four studies were considered eligible. These studies involved a total of 154 patients with 597 dental implants and a mean follow-up period of 2.25 years. There was no difference between computer-guided surgery and freehand surgery in terms of the marginal bone loss (mean difference −0.11 mm, 95% confidence interval (CI) −0.27 to 0.04 mm; P = 0.16), mechanical complications (risk ratio (RR) 0.85, 95% CI 0.36–2.04; P = 0.72), biological complications (RR 1.56, 95% CI 0.42–5.74; P = 0.51), and implant survival rate (RR 0.53, 95% CI 0.11–2.43; P = 0.41). This meta-analysis demonstrated that both computer-guided and freehand surgeries yielded similar results for marginal bone loss, mechanical and biological complications, and implant survival rate.
Keywords: Computer-guided surgery; Dental implants; Systematic review